Experiences of implant loss after immediate implant‐based breast reconstruction: qualitative study. Issue 3 (17th March 2020) - Mahoney, B.; Walklet, E.; Bradley, E.; Thrush, S.; Skillman, J.; Whisker, L.; Barnes, N.; Holcombe, C.; Potter, S.
Abstract : Background: Immediate implant‐based breast reconstruction (IBBR) is the most commonly performed reconstructive procedure in the UK, but almost one in ten women experience implant loss and reconstructive failure after this technique. Little is known about how implant loss impacts on patients' quality of life. The first phase of the Loss of implant Breast Reconstruction (LiBRA) study aimed to use qualitative methods to explore women's experiences of implant loss and develop recommendations to improve care. Methods: Semistructured interviews were conducted with a purposive sample of women who experienced implant loss after immediate IBBR, performed for malignancy or risk reduction across six centres. Interviews explored decision‐making regarding IBBR, and experiences of implant loss and support received. Thematic analysis was used to explore the qualitative interview data. Sampling, data collection and analysis were undertaken concurrently and iteratively until data saturation was achieved. Results: Twenty‐four women were interviewed; 19 had surgery for malignancy and five for risk reduction. The median time between implant loss and interview was 42 (range 22–74) months. Ten women had undergone secondary reconstruction, two were awaiting surgery, and 12 had declined further reconstruction. Three key themes were identified: the need for accurate information about the risks and benefits of IBBR; the need for more information about 'early‐warning' signs of postoperative problems, to empower women to seek help; and better support following implant loss. Conclusion: Implant loss is a devastating event for many women. Better preoperative information and support, along with holistic patient‐centred care when complications occur, may significantly improve the experience and outcome of care. Abstract : Immediate implant‐based breast reconstruction is the most commonly performed reconstructive procedure worldwide after mastectomy for breast cancer, but up to one in ten women experience implant loss and reconstructive failure after this technique. This qualitative study explores the experiences of 24 women experiencing implant loss from six centres across the UK. It highlights the need for more balanced presentation of the risks and benefits of different techniques to inform decision‐making, the need for better information regarding the early signs of potential problems to empower women to seek help, and more support for patients experiencing this potentially devastating complication. Patients need better support Abstract : Antecedentes: La reconstrucción mamaria inmediata con prótesis ( implant‐based breast reconstruction, IBBR) es el procedimiento reconstructivo más utilizado en el Reino Unido, pero casi una de cada diez mujeres presentará pérdida de la prótesis y fallo del procedimiento reconstructivo tras esta técnica. Se sabe poco de cómo la pérdida de la prótesis afecta la calidad de vida de las pacientes. La primera fase del estudio LiBRA tuvo como objetivo explorar la percepción de las mujeres ante la pérdida de la prótesis, utilizando métodos cualitativos, y proponer una serie de medidas para mejorar la atención sanitaria de estas pacientes. Métodos: Se realizaron entrevistas semiestructuradas en una muestra de mujeres que padecieron la pérdida de la prótesis tras una IBBR inmediata, realizada por neoplasia o como procedimiento de reducción de riesgo, en seis centros. Las entrevistas analizaron la toma de decisiones con respecto a la IBBR inmediata, así como la percepción ante la pérdida del implante y el soporte recibido. Se utilizó un análisis por temas para examinar los datos de la entrevista cualitativa. El muestreo, la recopilación de datos y el análisis se realizaron de forma simultánea e iterativa hasta que se logró la saturación de datos. Resultados: Se entrevistaron 24 pacientes; 19 en las que la indicación quirúrgica fue por cáncer y 5 por reducción de riesgo. La mediana del tiempo entre la pérdida del implante y la entrevista fue de 42 (rango 22‐52) meses. Diez mujeres se habían sometido a una reconstrucción secundaria; dos estaban a la espera de la cirugía y 12 habían rechazado la reconstrucción posterior. Se identificaron tres temas clave, siendo las necesidades de: i) información precisa sobre los riesgos y beneficios de la IBBR, ii) más información sobre los signos de "alarma precoz" de las complicaciones postoperatorias que permitiesen a las mujeres buscar ayuda, y iii) mejor soporte tras la pérdida de la prótesis. Conclusión: La pérdida de una prótesis es una complicación catastrófica para muchas mujeres. Una mejor información y apoyo preoperatorios, junto con una atención holística centrada en la paciente cuando se presentan las complicaciones, podrían mejorar significativamente la experiencia y el resultado de la atención.